PERANCANGAN UI/UX WEBSITE DALAM MANAGEMENT APLIKASI GYM MENGGUNAKAN METODE DESIGN THINKING - Tuhfah Humaira Mufidah; Nuur Wachid Abdul Majid (Jurnal Media Infotama, 2023)
In Indonesia, there are many services that provide fitness services. However, only a few have implemented technological sophistication such as the absence of mobile applications and manual admin management. This causes few business units in Indonesia to be able to retain customers due to the lack of management in the gym business unit. Management in gym services is the main focus to improve performance and quality in the business so that it can be properly designed with the right calculations as well, with the existence of technological sophistication can help these problems by developing a website for admin management in the gym business. The design uses the design thinking method which includes the empathize, define, ideate, prototype, test stages by conducting tests to find out how easy, efficient, easy to remember, and errors or security of the designed website. Testing is done by interviewing users directly. So that it can be immediately implemented in real terms and can continue to be evaluated to improve admin performance.